Spatial variation in the distribution of gas stations in the municipality of Al-Ajeelat, geographical analysis using GIS (Journal of Libya for geographical studies, 2024)
The research aims to analyze the spatial reality of those stations and their ability to meet the fuel needs of the population, while building an updatable and developable geographic information database. The research follows the analytical methodology along with field studies to achieve more accurate results using Geographic Information Systems (GIS) technology. One of the most important findings is the dominance of medium-sized stations, accounting for 61% of the total number of fuel stations (23 stations), with no specific consistent trend in their distribution. It also reveals a high density of distribution concentrated in the north and northeast, with overlapping service coverage, which confirms the lack of implementation of some planning standards and access to recommendations. These include the development of successful plans and proposals to identify strengths and weaknesses in the current and future distribution and work on finding quick and feasible solutions for all inactive stations to achieve fairness in fuel distribution to all residents, taking into account planning standards when establishing fuel stations.
Keywords: Geographic Information Systems (GIS); planning standards; nearest neighbor analysis; scattered distribution; spatial range, density